Early Developmental PMCA2b Expression Protects From Ketamine-Induced Apoptosis and GABA Impairments in Differentiating Hippocampal Progenitor Cells - Lisek, Malwina; Mackiewicz, Joanna; Sobolczyk, Marta; Ferenc, Bozena; Guo, Feng; Zylinska, Ludmila; Boczek, Tomasz (Frontiers in Cellular Neuroscience, 2022)
PMCA2 is not expressed until late embryonic state when the control of subtle Ca2+ fluxes becomes important for neuronal specialization. During this period immature neurons are especially vulnerable to degenerative insults induced by NMDA receptor blocker – ketamine. H19-7 hippocampal progenitor cells isolated from E17 do not express PMCA2 isoform, hence they constitute a valuable model for studying its role in neuronal development. Here we demonstrated that heterologous expression of PMCA2b enhanced differentiation of H19-7 cells and protected from ketamine-induced death. PMCA2b did not affect resting [Ca2+]c in the presence or absence of ketamine and had no effect on the rate of Ca2+ clearance following membrane depolarization in the presence of the drug. The up-regulation of endogenous PMCA1 demonstrated in response to PMCA2b expression as well as ketamine-induced PMCA4 depletion were indifferent to the rate of Ca2+ clearance in the presence of ketamine. Yet, co-expression of PMCA4b and PMCA2b was able to partially restore Ca2+ extrusion diminished by ketamine. The profiling of NMDA receptor expression showed up-regulation of NMDAR1 subunit in PMCA2b-expressing cells and increased co-immunoprecipitation of both proteins following ketamine treatment. Further microarray screening demonstrated significant influence of PMCA2b on GABA signaling in differentiating progenitor cells manifested by the unique regulation of several genes key to the GABAergic transmission. The overall activity of GAD remained unchanged but Ca2+-induced GABA release was inhibited in the presence of ketamine. Interestingly, PMCA2b expression was able to reverse this effect. The mechanism of GABA secretion normalization in the presence of ketamine may involve PMCA2b-mediated inhibition of GABA transaminase, thus shifting GABA utilization from energetic purposes to neurosecretion. In this paper, we show for the first time that developmentally-controlled PMCA expression may dictate the pattern of differentiation of hippocampal progenitor cells. Moreover, the appearance of PMCA2 earlier is development has long-standing consequences for GABA metabolism with yet unpredictable influence on GABAergic neurotransmission during later stages of brain maturation. On the other hand, the presence of PMCA2b seems to be protective for differentiating progenitor cells from ketamine-induced apoptotic death.